2018
DOI: 10.1186/s12889-018-5346-4
|View full text |Cite
|
Sign up to set email alerts
|

Design, implementation and evaluation of a web-based computer-tailored intervention to prevent binge drinking in adolescents: study protocol

Abstract: BackgroundBinge-drinking in adolescents is a highly prevalent healthcare problem that associates physical and mental health complications with community implications. This paper describes the design, implementation and evaluation of the first web-based computer tailored intervention aimed at the prevention of binge drinking in Spanish adolescents.MethodsThe Alerta Alcohol program is based on the I-Change Model. First, feedback from focus and Delphi groups are used for cultural adaptation and to obtain further … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 48 publications
0
31
0
1
Order By: Relevance
“…Data from a longitudinal study, a two-arm cluster randomized controlled trial with an intervention group (IG) and a control group (CG) randomized at the school level, for prevention of BD in adolescents known as Alerta Alcohol were used in this work (more information about the design of the study can be obtained from the published study protocol; see Lima-Serrano et al, 2018) [29]. Alerta Alcohol is a web-based computer-tailored programme consisting of six sessions, of which sessions 1 and 6 consist of assessment questionnaires and sessions 2 to 5 are aimed at providing feedback through preventive messages and personalized information to intervene on alcohol use.…”
Section: Design and Samplementioning
confidence: 99%
“…Data from a longitudinal study, a two-arm cluster randomized controlled trial with an intervention group (IG) and a control group (CG) randomized at the school level, for prevention of BD in adolescents known as Alerta Alcohol were used in this work (more information about the design of the study can be obtained from the published study protocol; see Lima-Serrano et al, 2018) [29]. Alerta Alcohol is a web-based computer-tailored programme consisting of six sessions, of which sessions 1 and 6 consist of assessment questionnaires and sessions 2 to 5 are aimed at providing feedback through preventive messages and personalized information to intervene on alcohol use.…”
Section: Design and Samplementioning
confidence: 99%
“…Social influences consist of the perception of others carrying out this type of behaviour (social modelling), the norms that people have with respect to these behaviours (social norms) and the perceived pressure from the environment (social pressure). Self-efficacy refers to a person's perception of their capability to carry out the type of behaviour [18,19]. Motivational factors are determined by various awareness factors (knowledge, risk perceptions and cues to action), predisposing factors (behavioural, psychological, biological, social and cultural factors) and information factors [17].…”
Section: Introductionmentioning
confidence: 99%
“…The sample was part of a two-arm cluster randomized controlled trial that evaluated an intervention aimed at reducing binge drinking among adolescents (aged [15][16][17][18][19] in Andalusian secondary schools through a web-based computer-tailored programme known as Alerta Alcohol (more information about the design of the study may be found in Lima-Serrano et al (2018) [17]). A total of 1,247 adolescents from 15 public high schools were assessed at baseline (January-February, 2017) and 612 adolescents at 4-month follow up (May-June, 2017).…”
Section: Design Population and Samplementioning
confidence: 99%
“…Heavy episodic drinking (HED) (de ned as drinking ve or more drinks, 60 or more grams of pure alcohol, on at least one occasion at least once per month) among young people aged 15 to 19 years is particularly prevalent in Europe (24.1%) [1]. Despite reductions in HED among adolescents (15)(16)(17)(18)(19)…”
Section: Introductionmentioning
confidence: 99%